Resilience and Regional Dynamics An International Approach to a New Research Agenda (Advances in Spatial Science, The Regional Science Series,, 2018)
Economic and financial crises have brought the rise of unemployment, reduction of economic growth and emergence of global imbalances and tensions as countries and regions have suffered the effects of a variety of internal and external shocks. In this context of constant disruption, the scientific community has struggled to provide satisfactory answers to current economic challenges within standard frameworks. Focusing on the interconnections between innovation and resilience, this edited book contributes to a better understanding of how the crisis affects innovation and the capacity of territories to adapt and evolve. It offers both theoretical and empirical contributions that debate the notions of resilience in regional and urban contexts and serve as case studies related to innovation strategies and territorial clusters.